Role of Lymphadenectomy During Interval Debulking Surgery Performed After Neoadjuvant Chemotherapy in Patients With Advanced Ovarian Cancer - He, Minjun; Lai, Yuerong; Peng, Hongyu; Tong, Chongjie (Frontiers in Oncology, 2021)
Objective. The role of lymphadenectomy in interval debulking surgery (IDS) performed after neoadjuvant chemotherapy (NACT) in advanced ovarian cancer remains unclear. We aimed to investigate the clinical significance of lymphadenectomy in IDS. Methods. We retrospectively reviewed and analyzed the data of patients with advanced ovarian cancer who underwent NACT followed by IDS. Results. In 303 patients receiving NACT-IDS, lymphadenectomy was performed in 127 (41.9%) patients. One hundred and sixty-three (53.8%) patients achieved no gross residual disease (NGRD), and 69 (22.8%) had residual disease < 1 cm, whereas 71 (23.4%) had residual disease ≥ 1cm. No significant difference in progression-free survival (PFS) and overall survival (OS) was observed between the lymphadenectomy group and the no lymphadenectomy group in patients with NGRD, residual disease < 1 cm, and residual disease ≥ 1 cm, respectively. The proportions of pelvic, para-aortic and distant lymph node recurrence were 7.9% (10/127), 4.7% (6/127) and 5.5% (7/127) in the lymphadenectomy group, compared with 5.7% (10/176, P = 0.448), 4.5% (8/176, P = 0.942) and 5.1% (9/176, P = 0.878), respectively, in no lymphadenectomy group. Multivariate analysis identified residual disease ≥ 1 cm [hazard ratios (HR), 4.094; P = 0.008] and elevated CA125 levels after 3 cycles of adjuvant chemotherapy (HR, 2.883; P = 0.004) were negative predictors for OS. Conclusion. Lymphadenectomy may have no therapeutic value in patients with advanced ovarian cancer underwent NACT-IDS. Our findings may help to better the therapeutic strategy for advanced ovarian cancer. More clinical trials are warranted to further clarify the real role of lymphadenectomy in IDS.